Advances in sensing and processing methods for three-dimensional robot vision. (19th March 2018) - He, Yu; Chen, Shengyong
In this article, we survey the recent developments of sensing methods in three-dimensional robot vision, centering on the current three-dimensional sensors and core techniques embedded in robotic systems. Over 8000 publications have reported rather wide application areas of three-dimensional robot vision in the last 40 years, such as human–robot interaction, object recognition, three-dimensional modeling, object tracking, searching and surveillance, as well as robot manipulation, localization, navigation, mapping, and path planning. Representative works and future research trends are also addressed in this article.